2022
DOI: 10.3390/ma15103727
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of 3D-Printed Materials’ Structural Properties Using Active Infrared Thermography and Deep Neural Networks Trained on the Numerical Data

Abstract: This article describes an approach to evaluating the structural properties of samples manufactured through 3D printing via active infrared thermography. The mentioned technique was used to test the PETG sample, using halogen lamps as an excitation source. First, a simplified, general numerical model of the phenomenon was prepared; then, the obtained data were used in a process of the deep neural network training. Finally, the network trained in this manner was used for the material evaluation on the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Microwave heating has been widely employed in the literature for various purposes related to concrete structures, including expediting the curing process, decontaminating cement, and facilitating the drilling or melting of concrete [24][25][26][27]. In this proposal, microwaves are suggested as a potential energy source for infrared thermography [28][29][30][31][32][33][34]. The primary benefit of utilizing microwave heating lies in its volumetric nature.…”
Section: Active Thermography Methodsmentioning
confidence: 99%
“…Microwave heating has been widely employed in the literature for various purposes related to concrete structures, including expediting the curing process, decontaminating cement, and facilitating the drilling or melting of concrete [24][25][26][27]. In this proposal, microwaves are suggested as a potential energy source for infrared thermography [28][29][30][31][32][33][34]. The primary benefit of utilizing microwave heating lies in its volumetric nature.…”
Section: Active Thermography Methodsmentioning
confidence: 99%
“…This limits the applicability of UT because LPBF-printed metals have rough surfaces due to the specifics of the manufacturing process. Pulsed infrared thermography (PIT) or the active thermography NDE method use non-contact sensors for the imaging of subsurface defects in optically opaque materials [21][22][23][24][25][26][27][28]. PIT uses a flash lamp to deposit a thermal pulse on a material surface.…”
Section: Introductionmentioning
confidence: 99%
“…In classification tasks, features extracted from images are used to assign a predefined class value to the input image, and in regression tasks, the features extracted from CNNs are used to predict appropriate continuous values. In prior studies, CNN was shown to be an efficient method for analysis of images for in situ monitoring of AM [8][9][10][11][12], and NDE of AM [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%